2022
DOI: 10.1002/fsn3.2781
|View full text |Cite
|
Sign up to set email alerts
|

Sodium in relation with nonalcoholic fatty liver disease: A systematic review and meta‐analysis of observational studies

Abstract: Findings on the association of sodium with nonalcoholic fatty liver disease (NAFLD) are conflicting. The present systematic review and meta‐analysis study aimed to assess the association between salt or sodium intake or serum sodium levels and NAFLD risk. Relevant articles were identified by searching PubMed, Web of Knowledge, Scopus, Proquest, and Embase databases through May 1, 2021, without language restriction. The pooled odds ratio (OR) and 95% confidence interval (CI) were estimated using Der‐Simonian an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 72 publications
(135 reference statements)
1
8
0
Order By: Relevance
“…During the preparation of this review, Shojaei-Zarghani et al [ 5 ] published a systematic review with a meta-analysis evaluating the effect of sodium on NAFLD prevalence that mostly agreed with our thoughts. The main results of the study by Shojaei-Zarghani et al [ 5 ] were: higher risk of developing NAFLD in high- sodium intake compared to low intake (OR = 1.6, 95% CI: 1.19–2.15); surveys using predictive formulas (FLI) to assess NAFLD showed a higher effect size (OR = 2.02, 95% CI: 1.29–3.17) than those assessing disease by FibroScan or ultrasonography (OR = 1.81, 95% CI: 1.24–2.65); studies with sodium excretion (24 h and <24 h) showed a higher risk of developing NAFLD (OR = 2.48, 95% CI: 1.52–4.06, I2 = 96.00%) compared with dietary assessments of sodium (OR = 1.23, 95% CI: 1.15–1.32). It is important to point out that these data refer to the uncorrected risk ratio and that the assessment of the certainty of the evidence (assessed by the GRADE method) was considered very low, so these data should be evaluated with great caution.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…During the preparation of this review, Shojaei-Zarghani et al [ 5 ] published a systematic review with a meta-analysis evaluating the effect of sodium on NAFLD prevalence that mostly agreed with our thoughts. The main results of the study by Shojaei-Zarghani et al [ 5 ] were: higher risk of developing NAFLD in high- sodium intake compared to low intake (OR = 1.6, 95% CI: 1.19–2.15); surveys using predictive formulas (FLI) to assess NAFLD showed a higher effect size (OR = 2.02, 95% CI: 1.29–3.17) than those assessing disease by FibroScan or ultrasonography (OR = 1.81, 95% CI: 1.24–2.65); studies with sodium excretion (24 h and <24 h) showed a higher risk of developing NAFLD (OR = 2.48, 95% CI: 1.52–4.06, I2 = 96.00%) compared with dietary assessments of sodium (OR = 1.23, 95% CI: 1.15–1.32). It is important to point out that these data refer to the uncorrected risk ratio and that the assessment of the certainty of the evidence (assessed by the GRADE method) was considered very low, so these data should be evaluated with great caution.…”
Section: Discussionsupporting
confidence: 67%
“…There are few human and animal studies dealing with the influence of sodium consumption on the development of NAFLD. Shojaei-Zarghani et al [ 5 ], in a systematic review and meta-analysis of observational studies, found that people with a high-sodium intake have a 60% greater risk of developing NAFLD compared to those with low consumption. Xu and Mao [ 6 ] reviewed the potential mechanisms for this relationship: elevation of caloric consumption, hyperosmolarity induced by salt, insulin resistance, endogenous fructose synthesis, and dysfunction of the RAAS.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also demonstrated that high sodium intake is associated with the risk of NAFLD [ 60 ] . Uetake et al [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, estrogen deficiency induces metabolic disturbance in energy, glucose, lipid, and bone metabolism [21]. A high salt intake exacerbates metabolic dysfunction [13,31]. Although their relationship remains controversial, a high salt intake induces hypertension in salt-sensitive persons.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen or phytoestrogen intervention prevented the estrogen-deficient-related symptoms [21,22,29]. On the other hand, a high sodium intake increases the salt sensitivity to hypertension, exacerbating metabolic syndrome, even though women are salt insensitive before menopause [31]. Furthermore, the salt sensitivity to hypertension is inversely correlated with the circulating ovarian hormones [37].…”
Section: Discussionmentioning
confidence: 99%